2012
DOI: 10.1073/pnas.1209647109
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomes of germinal zones of human and mouse fetal neocortex suggest a role of extracellular matrix in progenitor self-renewal

Abstract: The expansion of the neocortex during mammalian brain evolution results primarily from an increase in neural progenitor cell divisions in its two principal germinal zones during development, the ventricular zone (VZ) and the subventricular zone (SVZ). Using mRNA sequencing, we analyzed the transcriptomes of fetal human and embryonic mouse VZ, SVZ, and cortical plate. In mouse, the transcriptome of the SVZ was more similar to that of the cortical plate than that of the VZ, whereas in human the opposite was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
380
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(406 citation statements)
references
References 51 publications
(92 reference statements)
25
380
1
Order By: Relevance
“…However, more recent studies in ferret (Reillo and Borrell, 2012) and macaque (Betizeau et al, 2013) have shown that the cellular composition of ISVZ and OSVZ is very similar and both contain oRG and IPCs than was previously appreciated. This is also in agreement with the finding that gene expression profiles of ISVZ and OSVZ in the human developing neocortex are closely related to each other (Fietz et al, 2012; Miller et al, 2014). …”
Section: Does the Isocortex Of All Eutherian Mammals Develop From A Gsupporting
confidence: 91%
See 2 more Smart Citations
“…However, more recent studies in ferret (Reillo and Borrell, 2012) and macaque (Betizeau et al, 2013) have shown that the cellular composition of ISVZ and OSVZ is very similar and both contain oRG and IPCs than was previously appreciated. This is also in agreement with the finding that gene expression profiles of ISVZ and OSVZ in the human developing neocortex are closely related to each other (Fietz et al, 2012; Miller et al, 2014). …”
Section: Does the Isocortex Of All Eutherian Mammals Develop From A Gsupporting
confidence: 91%
“…In the brain, transcriptomes from the whole cerebral cortex, and developing neocortical brain compartments (ventricular zone, subventricular zone, and cortical plate, CP), exhibit different sets of transcripts. Developmental compartments have been shown to express specific gene‐signatures (Ayoub et al, 2011; Fietz et al, 2012) differing across ontogeny. Thus, a cohort of active transcripts during development and in adult cortical compartments can be differentiated at the level of gene expression, splicing, and RNA editing (Dillman et al, 2013).…”
Section: Exploring Brain Evolution From Transcriptome Databasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though any given germinal layer contains a variety of cortical progenitors and other cell types, this first approximation identified thousands of genes expressed in germinal layers at different relative levels between mouse and human. Significantly, this study also led to the intriguing finding that extracellular matrix (ECM) components are highly enriched in the OSVZ of the human fetal cortex compared with mouse (Fietz et al, 2012). Importantly, experiments performed in ferret demonstrate that signaling via ECM components, fibroblast‐ and platelet‐derived growth factors is directly involved in promoting the hyper‐proliferation and/or self‐renewal of cortical progenitors in gyrencephalic species (Fietz et al, 2010; Lui et al, 2014; Rash et al, 2013; Stenzel et al, 2014).…”
Section: Molecular Regulation: Evo‐devo Lessons From Transcriptomicsmentioning
confidence: 89%
“…As a first approximation, a landmark study reported the content of the whole transcriptome of individual cortical germinal layers in both mouse and human fetuses, and compared their composition (Fietz et al, 2012). Even though any given germinal layer contains a variety of cortical progenitors and other cell types, this first approximation identified thousands of genes expressed in germinal layers at different relative levels between mouse and human.…”
Section: Molecular Regulation: Evo‐devo Lessons From Transcriptomicsmentioning
confidence: 99%